Energy Flux: The Link between Multitrophic Biodiversity and Ecosystem Functioning. (March 2018) - Barnes, Andrew D.; Jochum, Malte; Lefcheck, Jonathan S.; Eisenhauer, Nico; Scherber, Christoph; O'Connor, Mary I.; de Ruiter, Peter; Brose, Ulrich
Abstract : Relating biodiversity to ecosystem functioning in natural communities has become a paramount challenge as links between trophic complexity and multiple ecosystem functions become increasingly apparent. Yet, there is still no generalised approach to address such complexity in biodiversity–ecosystem functioning (BEF) studies. Energy flux dynamics in ecological networks provide the theoretical underpinning of multitrophic BEF relationships. Accordingly, we propose the quantification of energy fluxes in food webs as a powerful, universal tool for understanding ecosystem functioning in multitrophic systems spanning different ecological scales. Although the concept of energy flux in food webs is not novel, its application to BEF research remains virtually untapped, providing a framework to foster new discoveries into the determinants of ecosystem functioning in complex systems. Highlights: Incorporating natural complexity into BEF research is a key challenge in ecology. Energy flux dynamics in networks underpin BEF theory in multitrophic systems. Network energetics define stability and functions across ecological scales, allowing for the expansion of BEF research to complex systems. We propose future directions for integrating network energy fluxes into BEF research.